Choosing brave : how Mamie Till-Mobley and Emmett Till sparked the civil rights movement - Joy, Angela, 1975- (Roaring Brook Press, 2022)
A non-fiction picture book telling the story of Emmet Till, an African American boy brutally lynched and killed in 1955, and his mother, Mamie Till-Mobley, who took her pain and sorrow over the murder of her son and made it into a rallying cry for the Civil Rights Movement at the time. Champions and celebrates Mamie's fearlessness and bravery in not letting her son's death be forgotten.